Clinical Evaluation of Medavriddhi in Hyperlipidemia and its Management with Lekhaniya Mahakashaya. - Paul, Sumana Ray; Ray, Sukalyan (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Dhatus are the structural and functional units of human body. The healthy state of body depends on their equilibrium state whereas disequilibrium in Dhatus leads to pathological conditions and diseases. Meda is one of the seven Dhatus of human body which is produced from its precursor Asthi Dhatu. Meda Dhatu can be correlated with lipids and lipoproteins. The state of hyperlipidaemia can be correlated with the state of Meda Vriddhi. Aims and Objectives: This study was carried out to clinically evaluate the features of Meda Vriddhi in individuals having hyperlipidaemia as well as to evaluate the efficacy of stipulated poly herbal formulation ‘Lekhaniya Kashayam’ to combat the state of Meda Vriddhi and subsequently hyperlipidaemia. Materials and Methods: 35 subjects having hyperlipidaemia have been selected for the study based on inclusion and exclusion criteria and subsequently the features of Meda Vriddhi has been clinically evaluated in those subjects. The stipulated poly herbal preparation ‘Lekhaniya Kashaya’ was administered in a dose of 50 ml as warm decoction, thrice daily for 60 consecutive days. The efficacy of the drug was evaluated after 60 days based on subjective and objective parameters. Result and Discussions: The subjective parameters of Meda Vriddhi are clinically present in maximum number of individuals having hyperlipidaemia. The result also reveals the significant efficacy of the ‘Lekhaniya Ksahaya’ on relevant subjective and objective parameters with a ‘p’ value <0.001 in the majority of subjective and objective parameters. Conclusions: The state of hyper lipidaemia can be compared with the state of Meda Vriddhi based on the presence of Meda Vriddhi Lakshana in subjects having hyper lipidaemia. The therapeutic management with Lekhaniya Kashaya can be equally effective to combat the state of Meda Vriddhi as well as hyper lipidaemia.